The LEADER process as a European policy for local development: A comparison of the implementation in three European member states - Marielle Berriet-Solliec; Catherine Laidin; Denis Lépicier; Hai Vu Pham; Kim Pollermann; Petra Raue; Gitta Schnaut (European Regional Science Association (ERSA), 2015)
New governance structures, meant to empower local decision makers, are supported by some policies introduced by the European Commission. LEADER, from rural development policy, is among these approaches. Nevertheless, these new policies are implemented in very different multi-level governance contexts in the European nation states. We question in how far the institutional differences on the different levels affect the implementation of LEADER on the local level. We thereby hope to contribute to a better understanding of the causes and consequences of differences in the impacts and effectiveness of the LEADER approach as has been documented thus far by research analyses. In our TRUSTEE research project we concentrate on ten cases in France, Germany and Italy. We describe the three different administration systems and the different types of RDP-implementation. Based on analyses of documents and interviews with stakeholders, we then analyze the possible relation of these institutional differences to the LEADER implementation at a local level.
Additional information: Revised version / erweiterte & überarbeitete Version; Older version: http://hdl.handle.net/10419/124740
Keywords: H11; R58; 330; rural development; multi-level governance; European policy; decentralization; Ländliche Entwicklung; Governance-Ansatz